Analysis of Gases and Airs from Collieries (The Australasian Institute of Mining and Metallurgy, 1983)
The Coke Ovens Laboratory at Australian Iron & Steel, Port Kembla has been involved in the analysis of seam gases and mine airs for approximately twenty (20) years. This period has seen many developments and changes in the techniques used to the point when the current techniques are equal to other labora- tories involved in similar analyses. The laboratory has NATA registration for the analysis of mine airs and gases. Apart from routine testing of seam gases, ventilation airs and gases emmitted from coal bore cores a number of projects have been undertaken. These have served a twofold purpose, one to provide information to the customer, generally Collieries Research and Technology and secondly in developing the skills and capabilities of the Coke Ovens Laboratory. This paper discusses the development and services available at the Coke Ovens Laboratory for the analysis of gases and airs from collieries.